Study of solid-state transformer - Choo, Ren You (2018)
Transformers are used to control the network voltages by changing the transformation ratio. The conventional transformers are able to perform very well in regulating the voltages by either stepping up or down voltages within certain limits depending on the transformation ratio [1], [2]. They have a few advantages such as being inexpensive and also highly reliable due to their components. However, due to its large volume and weight, it will affect the performance of certain applications such as the locomotives. Hence, solid state transformer was introduced as an alternate solution to replace the regular transformer, due to its lightweight and small in size. The Solid State Transformer also includes additional features such as harmonic compensation, power factor correction,etc [1], [2], [3]. A study was conducted at the University of Arkansas to evaluate Solid State Transformer topologies to establish their suitability for applications in electric power distribution systems [1]. The results of the study show that the Solid State Transformer based on boost converter topology had the highest efficiency but requires more power electronics component as compared the other topologies, consequently affecting the cost of the system [1]. Therefore, it is important to consider the cost and system efficiency of the Solid State Transformer while designing the suitable topology.